Recursos didácticos tecnológicos para el pensamiento lógico matemático - Tipanluisa Arequipa, Jessica Magaly (2023)
The present investigation focused on the study of technological didactic resources for mathematical logical thinking, because this aspect of learning and development is essential to be able to analyze and solve problems that arise in everyday life. The objective of the research was to identify the benefits of the use of technological didactic resources to improve the level of development of mathematical logical thinking of the students of the Third Year of EGB of the Rioblanco Alto Educational Unit. The applied methodology was based on the quantitative approach that is based on the analysis of numerical data, the type of research was correlational, the sample consisted of 16 teachers and 35 students, the techniques used were the survey of teachers and the observation of the students. The results of the research show that in the educational institution there is a low level of knowledge about technological teaching resources, therefore, they are not used frequently within the teaching-learning process of mathematics, to promote the development of thinking. mathematical logician. By incorporating these resources, a higher level of interest and participation of the students was evidenced, which allowed improving skills in terms of pattern reproduction, the representation of ordered pairs, numbers and quantities, measurement, comparison and resolution of mathematical problems.